Silibinin ameliorates deoxycholic acid-induced pyroptosis in steatotic HepG2 cells by inhibiting NLRP3 inflammasome activation - Meiqing Mai; Ya Wang; Mengliu Luo; Zhongxia Li; Di Wang; Yongdui Ruan; Honghui Guo (Biochemistry and Biophysics Reports, 2023)
Nonalcoholic steatohepatitis (NASH) represents an inflammatory subtype of nonalcoholic fatty liver disease (NAFLD). The activation of the NOD-like receptor protein 3 (NLRP3) inflammasome triggers pyroptosis, thus propelling the progression from simple steatosis to NASH. Silibinin, a hepatoprotective compound derived from milk thistle, exerts diverse hepatoprotective effects. However, the direct impact of silibinin on NLRP3 inflammasome activation and its ability to mitigate pyroptosis remain uncertain. To address this, we utilized an in vitro model of NASH, employing HepG2 cells treated with deoxycholic acid (DCA) and free fatty acids. Subsequently, we treated these model cells with silibinin for 24 h. Our findings demonstrated that, although there were no significant changes in cellular lipid content, silibinin effectively ameliorated hepatocyte injuries. Silibinin treatment inhibited the activation of the NLRP3 inflammasome and suppressed DCA-induced pyroptosis. Additionally, molecular docking analysis revealed that silibinin exhibited a binding affinity to components of the NLRP3 inflammasome similar to that of MCC950, a selective NLRP3 inhibitor. These results suggest that silibinin may alleviate inflammation in DCA-exposed HepG2 cells by mitigating pyroptosis, possibly through its binding affinity and inhibition of the NLRP3 inflammasome. Overall, our study indicates that silibinin holds promise as a therapeutic agent for NASH by modulating pyroptosis and inhibiting NLRP3 inflammasome activation.